Inspired by Malacca Straits Mosque / Aiiman Fasha Ariff - Ariff, Aiiman Fasha (2022)
Malacca Straits Mosque Is a mosque located on the manmade Malacca Island In Malacca City. Malacca. Malaysia. It was built using the mix of Middle Eastern and Malay craftsmanship and looks like a floating structure when the water level is high. Its structure has two Intersecting archways lead to the main entrance and stained glass which covers the space In between the arches. The mosque compound has a 30-metre tall minaret that is also used as a lighthouse.